UTILIZATION OF BINAHONG (ANREDERA CORDIFOLIA (TEN.) STEENIS) LEAVES EXTRACT AS HERBAL MEDICINE VIA ULTRASONICATION - Nury, Dennis Farina; Luthfi, Muhammad Zulfikar (Universitas 17 Agustus 1945 (UNTAG) Semarang, 2024)
The leaves of Anredera cordifolia, or binahong, are one of the herbal plants with a high potential for antioxidants and have been reported to be rich in flavonoids. This study aimed to determine the best operating conditions in the ultrasonication extraction method from binahong leaves extract on the yield obtained. Experiments were conducted into how extraction conditions affected the ultrasonication extraction of binahong leaves. Different extraction parameters, such as ethanol concentration (20–100%), time (10–40 min), temperature (30–70 C), and yield impacts, were used to extract powdered dried binahong leaves. The results showed all extraction parameters to have significant effects on yield obtained. The maximum yield of extract from binahong leaves was obtained at 60 ml of ethanol concentration, 20 minutes of extraction time, and 50°C ultrasonication bath temperature. Thus, it can be concluded that the ultrasonication process is a good way to obtain a better yield of simplicia of binahong leaves extract as a therapeutic herbal in the future.